Laser absorption spectroscopy of methane at 1000 K near 1.7 µm: A validation test of the spectroscopic databases. (August 2018) - Ghysels, M.; Vasilchenko, S.; Mondelain, D.; Béguier, S.; Kassi, S.; Campargue, A.
Highlights: A tubular furnace is combined with a diode laser absorption spectrometer. Spectra of methane are recorded at 964 K near 1.65 µm. The gas temperature is constant within a few K along the absorption path length. The 2-Temperature method is applied to identify high J transitions up to J  = 20. Comparisons with the HITRAN2016, MeCaSDa, TheoReTS, and ExoMol lists are discussed. Abstract: A tubular furnace is combined with a diode laser spectrometer to record the high temperature near infrared absorption spectrum of methane at a pressure of 80 Torr. The investigated spectral range covers the 5693–6257 cm −1 (1.75–1.60 µm) range of the tetradecad dominated by the 2ν3 band near 6000 cm −1 . Various determinations (thermocouples, Doppler line broadening, rotational temperature) provide a value of about 964 K for the gas temperature. Lines with intensity larger than 5 × 10 −24  cm/molecule at 1000 K are detected. As a result of the high temperature, high- J rovibrational transitions up to J  ≈ 20 and hot bands are identified in the spectrum. The recorded spectra provide tests of various methane line lists recently released in the literature: HITRAN2016, experimental list derived from emission spectra, the MeCaSDa empirical line list and the TheoReTs and ExoMol theoretical line lists. The agreement with the TheoReTs line list is found to be very good in the studied region. Graphical abstract: Image, graphical abstract